The underlying physics concept of a soccer game as a catalyst for enhancing creative thinking skills - Sriyanti, Ida; Afifa, Mardiah; Meilinda, Meilinda; Puteri, Anisya Sefina; Aisyah, Nyimas; Bayu, Wahyu Indra; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Hapizah, Hapizah (Institute of Advanced Engineering and Science, 2025)
Teachers need to improve students’ creative thinking skills by incorporating relevant everyday contexts. Soccer, as a familiar part of daily life, has not been widely used in education, and its impact on creative thinking requires further study. This research aimed to develop a contextual physics e-module centered on soccer to enhance creative thinking in physics learning. The study followed Rowntree's development model, including planning, development, and evaluation, with Tessmer’s formative evaluation through expert reviews, one-on-one assessments, small-group evaluations, and field tests. The creative thinking indicators used in the research are fluency, flexibility, originality, and elaboration. Data were collected from 346 high school students in Palembang via walkthroughs, questionnaires, and written tests, then analyzed using SPSS version 16. The results showed that the soccer-based physics e-module is valid (Sig. 0.00), practical (one-to-one: 82.75%; small group: 91.00%), and in the moderate category for improving creative thinking (N-gain: 0.59). These findings highlight the need to explore other everyday contexts and assess the long-term impact of the e-module across different educational settings.